THE RELATIONSHİP BETWEEN PROBLEM SOLVING LEVELS WITH DECISION MAKING STYLES OF SPORT MANAGERS (SPORTS ISTANBUL SAMPLE) - Adnan ERSOY; Taner ATASOY; Aydın PEKEL (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2018)
The aim of this study is to examine the relationship between the sport managers' skill of problem solving and decision-making styles. It constitutes 202 senior and middle level sports managers who work in the Istanbul Sports Activities and Business Trade Corporation in the Istanbul Metropolitan Municipality the universe of study. The sample of the study consists of 141 volunteer participants determined by random sampling method. In the study conducted by applying the scanning method (linked model) data were collected by survey method. Personal information form, developed to by Mann et al. [1998], adapted to Turkish by Deniz [2004] the Melbourne Decision Making Scale and developed by Heppner et al. [1982] adapted to Turkish by Şahin and Heppner [1993] the Problem-Solving Skill Scale was applied to the participants. The obtained data were recorded in the SPSS 23 package program. As a statistical process used correlation and regression analysis. As a result, it has been determined that the sport managers' decision-making style and problem-solving skills are at a good level, that there is a moderate relationship between decision making styles and problem-solving skills and that the sport managers decision-making style affect problem solving skills.